Estudio de la inclusión de estudiantes con discapacidad en la Universidad Nacional de Loja durante el año 2024. - Galeano Saldarriaga, Angie Katherine (2024)
This curricular integration study focuses on the examination of the inclusion of students with disabilities at the National University of Loja, with the aim of analyzing the existing conditions of inclusion within the institution. This research adopts a descriptive design with a mixed- methods approach, employing various methodological instruments such as surveys, interviews, and observation sheets to fulfill the objectives outlined in the study. The research findings reveal that the National University of Loja possesses limited inclusive infrastructure, which is insufficient to adequately address the specific needs of students, thereby impeding their full integration into the educational environment. On the other hand, the institution's faculty demonstrate limited knowledge regarding the methodological adaptations necessary to enhance the academic performance of students with disabilities. This lack of pedagogical preparation contributes to the dissatisfaction of the student population with specific needs regarding the inclusive education offered by the National University of Loja. The study underscores the urgent need to improve both the physical infrastructure and the social environment of the institution to foster effective inclusive education. Furthermore, it is imperative to train educators in adaptive methodologies that facilitate the learning of students with disabilities. Without appropriate planning and institutional commitment to inclusion, these students will continue to face significant barriers that limit their academic and personal development. Keywords: barriers, socio- educational, methodological adaptations, to train, inclusion.